2019
DOI: 10.1371/journal.pone.0214221
|View full text |Cite
|
Sign up to set email alerts
|

Potential value and limitations of different clinical scoring systems in the assessment of short- and long-term outcome following orthotopic liver transplantation

Abstract: BackgroundIn an attempt to further improve liver allograft utilization and outcome in orthotopic liver transplantation (OLT), a variety of clinical scoring systems have been developed. Here we aimed to comparatively investigate the association of the Balance-of-Risk (BAR), Survival-Outcomes-Following-Liver-Transplant (SOFT), Preallocation-Survival-Outcomes-Following-Liver-Transplant (pSOFT), Donor-Risk-Index (DRI), and the Eurotransplant-Donor-Risk-Index (ET-DRI) scores with short- and long-term outcome follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 32 publications
2
52
0
2
Order By: Relevance
“…11,12 Because of that, a careful selection and matching of donors and recipients are essential to improve allograft utilization and post-orthotopic liver transplantation (OLT) outcomes. 13 Recent studies by our group and others demonstrated a high prevalence of BC alterations in patients with end-stage liver disease. In particular, myosteatosis was identified as an important prognostic factor in predicting adverse perioperative outcomes in patients undergoing OLT.…”
Section: Introductionmentioning
confidence: 91%
“…11,12 Because of that, a careful selection and matching of donors and recipients are essential to improve allograft utilization and post-orthotopic liver transplantation (OLT) outcomes. 13 Recent studies by our group and others demonstrated a high prevalence of BC alterations in patients with end-stage liver disease. In particular, myosteatosis was identified as an important prognostic factor in predicting adverse perioperative outcomes in patients undergoing OLT.…”
Section: Introductionmentioning
confidence: 91%
“…The term ECD comprises a heterogenous group of different graft types with distinct functional impairments and an increased susceptibility to IRI [6,35]. Based on the growing obesity epidemic, steatotic grafts have emerged as an essential part of the ECD donor pool [36].…”
Section: The Heterogeneity Of Ecd Graftsmentioning
confidence: 99%
“…Boecker and associates aimed to comparatively investigate the association of Balance-of-Risk (BAR), Survival-Outcomes-Following-Liver-Transplant (SOFT), Preallocation-Survival-Outcomes-Following-Liver-Transplant (pSOFT), Donor-Risk-Index (DRI), and the Eurotransplant-Donor-Risk-Index (ET-DRI) scores with short-and long-term outcomes following LT. 52 Ninety-day mortality following LT was chosen as the primary endpoint for the assessment of the predictive abilities of the various scores. They included 328 LTs consecutively performed between 2010 and 2017 at a single institution in the analysis.…”
Section: Risk Factors and Outcome Predictorsmentioning
confidence: 99%
“…They suggested that only the BAR score could predict 90-day major morbidity and mortality with high accuracy (AUROC > 0.700). 52 Regarding biomarkers for prediction of post-LT outcomes, Baron-Stefaniak and coinvestigators studied whether the serum concentration of the cytokine Ddopachrome tautomerase (D-DT; or macrophage migration inhibitory factor [MIF]-2) in patients undergoing LT was associated with survival and acute kidney injury (AKI). 53 D-DT, a lymphokine, is a functional homologue of MIF, is ubiquitously stored in intracellular vesicles of human cells, and it is rapidly released into the circulating blood on stimulation.…”
Section: Risk Factors and Outcome Predictorsmentioning
confidence: 99%